Penatalaksanaan Fisioterapi Pada Kondisi Drop Foot Bilateral dengan Modalitas Infra Red, TENS dan Terapi Latihan - Mintasnim, Annisa; Luklukaningsih, Zuyina; Sari, Rima Yunita (Universitas Aufa Royhan, 2024)
Drop Foot is someone who is unable to lift the front foot when walking. This incident is reported to be around 19 per 100,000 people or 1% to 2% of all diagnosed sufferers. The aim of this research is to determine the management of physiotherapy with pain problems, limited range of motion of joints and decreased muscle strength. These problems are the reason researchers use selected modalities such as Infra Red, TENS and exercise therapy in the form of an ankle pump from February to March at the Bagas Waras Regional Hospital, Klaten. Collecting case study data on physiotherapy treatment using Infra Red modalities, TENS and exercise therapy in the form of an Ankle pump which resulted in reducing pressure pain in the 6th therapy (T6) to 1 from 4 (T0), increasing the range of joint movement by 5° at each meeting on the left side, as well as increasing muscle strength at the 6th therapy (T6) to a value of 3 from 1 (T0). Researchers advise the public to reduce activities such as lifting heavy weights in order to reduce the occurrence of spondylosis so that the number of Drop Foot cases does not continue to increase.